Job - Balentine, Samuel E. (Samuel Eugene), 1950- (Macon, Ga. : Smyth & Helwys Pub., 2006)
"The book of Job is considered by many to be the crown jewel of biblical literature in its claim to speak about God. The word that defines the challenge for every reader of the book is struggle. The struggle results from the fact that whatever Job's truth may be, he was neither the first nor the last to try to articulate it. In the midst of so many words in this world about God from writers within and outside the scriptural witness, this book offers a truly astonishing declaration about what it means to live in a world where order breaks down and chaos runs amok, where the innocent suffer and the wicked thrive, where cries for help go unanswered. This new commentary by biblical scholar Samuel Balentine leads readers on an in-depth and far-reaching look at the nature of the book of Job and the various attempts by the many who have sought to further explore Job's essential struggle ... the primary goal of the Smyth & Helwys Bible Commentary series is to make available serious, credible biblical scholarship in an accessible and less intimidating format. A visual generation of believers deserves a commentary series that contains not only the all-important textual commentary on Scripture, but images, photographs, maps, works of fine art, and drawings that bring the text to life. Each volume of the Smyth & Helwys Bible Commentary series features a CD-ROM, which expands the uses and capabilities of the Commentary even more"--Publisher description.
III. The third cycle: The dialogue breaks down (Job 22:1-27:23) -- Eliphaz's third response to Job: "Can a mortal be of use to God?" (Job 22:1-30 -- Job's response to Eliphaz: God is absent and evil runs amok (Job 23:1-24:25) -- Bildad's third speech and Job's response: Dominion, fear, and a whisper of something more (Job. 25:1-26:14) -- Job again: "May my enemy be like the wicked" (Job 27:1-23) -- A second soliloquy: "Where shall wisdom be found?" (Job 28:1-28) -- IV. Job's summation and decision to move beyond blessing and cursing (Job. 29:1-31:40) -- Past blessings (Job. 29:1-25) -- Present misery (Job 30:1-31) -- Job's declaration of innocence (Job 31:1-40) -- V. The speeches of Elihu (Job 32:1-37:24) -- The introduction of Elihu, the "answerer" (Job 32:1-22) -- The meaning of suffering (Job 33:1-33) -- God's just governance of the world (Job 34:1-37) -- God's detached justice (Job 35:1-16) -- Elihu's world (Job 36:1-37:24) -- VI. God's answer from the whirlwind and Job's response (Job 38:1-42:6) -- God's first answer: Job's first response (Job 38:1-40:5) -- God's second answer, Job's second response (Job 40:6-42:6) -- Epilogue: "As my servant Job has done" (Job 42:7-17).
Includes bibliographical references and indexes.
Print version record.
Keywords: Bible. -- Commentaries; Ijob <Buch>; Bible; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Commentaries; Electronic books